Eutectic‐derived bimodal porous Ni@NiO nanowire networks for high‐performance Li‐ion battery anodes. (9th September 2022) - Luo, Chang; Wang, Zigang; Chen, Yanxu; Zhao, Yanming; Han, Qiqi; Qin, Chunling; Wang, Zhifeng
Summary: Severe mechanical degradations and sluggish ion/electron migration are challenges for developing high‐performance NiO‐based anodes. Herein, by accelerating the solidification process of eutectic precursors, bimodal porous Ni@NiO nanowire networks containing refined one‐dimensional nanowire skeleton, abundant porous structure and large number of surface oxygen defects are obtained. The well‐designed porous networks can effectively adapt to the volumetric variation of electrode during cycling. In addition, the density functional theory computation confirms that oxygen vacancies play an important role in providing superior Li capture ability, enhancing the electrical conductivity and surface reactivity. Benefiting from the above advantages, the Ni@NiO‐45 anode presents impressive cycling stability, delivering a reversible capacity of 697.9 mAh g −1 after 100 cycles at a current density of 100 mA g −1 . The proposed structural regulating strategy in this study is anticipated to promote the exploitation of high‐performance conversion anodes and the application of dealloying technology in extensive fields. Abstract : Bimodal porous Ni@NiO nanowire networks containing one‐dimensional nanowire skeleton, abundant porous structure, and large number of surface oxygen defects are obtained, presenting good Li storage properties. The bimodal porous networks can adapt to the volumetric variation of electrode, while oxygen vacancies provide superior Li capture ability, enhancing the electrical conductivity and surface reactivity.